SOCIO-DEMOGRAPHIC DETERMINANTS OF ATTITUDE TOWARDS VOLUNTARY COUNSELLING AND TESTING (VCT) IN DELTA STATE, NIGERIA (Journal of Guidance and Counselling Studies, 2020)
There is no doubt whatsoever that the Human immunodeficiency virus infection is a pandemic infectious disease whose impact on societies is without precedent. Hence, people’s attitude towards HIV counselling and testing may significantly influence their willingness to participate and benefit from the services. Therefore, the study investigated Socio-demographic determinants of attitude towards voluntary counselling and testing in Delta State, Nigeria.The study adopted the cross-sectional descriptive survey design with a total sample size of two hundred (200) participants, selected simple random sampling. Instrument for data collection was a structured questionnaire titled Socio-demographic Determinants of Attitude towards Voluntary Counselling and Testing Questionnaire (SDAVCTQ). Univariate analysis was used to analyze quantitative variables using mean, and standard deviation and Bivariate analysis was used to analyze the relationship between the socio demographic variables and attitude of the respondents.Results of the study revealed that majority of the respondents have positive attitude towards VCT. It was also found that majority of the respondents were willing to recommend VCT to others while 83.5% believed VCT is very necessary. Finally the findings showed a high significant positive relationship between respondents' attitude and their socio-demographic characteristics such as annual income and tribe, while there is no significant relationship between respondents’ age, gender, marital status, educational level, occupation, religion and their attitude towards VCT.The study therefore concluded that there is a positive correlation between annual income, tribe and attitude of persons assessing voluntary counselling and testing of HIV. The study recommended among others that health workers and helping professionals such as medical doctors, nurses, counsellors, clinical psychologists and social welfare officers should be empowered with trainings to be abreast in recent scientific approaches in counselling and VCT centers should be decentralized to enable more people to benefit from the programme.
Keywords: Socio-demographic determinants; attitude; voluntary counselling and testing